Dual-Targeted Self-Assembled DNA Hydrogels Decorated With Multivalent Aptamers Loaded With DOX for Anticancer Therapy - Fangfang Jin; Qian Zeng; Husun Qian; Dian Zhang; Yu Wei; Yange Wang; Chengsen Chai; Wei Cheng; Shijia Ding; Tingmei Chen (Frontiers Media S.A., 2022)
Chemotherapy, as one of the principal modalities for cancer therapy, is limited by its non-specific and inefficient delivery to tumors. To overcome these limitations, we report herein a dual-targeted aptamer-decorated DNA hydrogel system (DTA-H) to achieve efficient, stable, and targeted delivery of drugs. Firstly, DNA hydrogel was formed by the rolling circle amplification. By reasonable design, double target and multivalent aptamers were decorated on DNA hydrogel to load DOX. The results confirmed that DTA-H can deliver chemotherapy drugs and aptamer nucleic acids drugs to target cells, inducing degradation of HER2 protein while chemotherapy is synergistic to inhibit HER2-positive breast cancer growth. The proposed drug delivery system has significant potential to achieve efficient, stable, and targeted delivery of drugs and cancer therapy.